2014
DOI: 10.7860/jcdr/2014/8349.4431
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell Distribution Width and Serum BNP Level Correlation in Diabetic Patients with Cardiac Failure: A Cross – Sectional Study

Abstract: Introduction: Red cell distribution width (RDW) is a red cell measurement given by fully automated hematology analyzers. It is a measure of heterogeneity in the size of circulating erythrocytes. Studies have shown that it is a prognostic marker in non -anemic diabetic patients with symptomatic cardiovascular disease but its correlation with cardiac failure in diabetics has not been studied so far. Moreover, studies have also shown that a higher RDW may reflect an underlying inflammatory state. Since Diabetes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Based on several studies, RDW is a marker of inflammation and prognosis in T2DM patients [ 43 , 44 ]. Subharshree et al initially examined the relationship between T2DM and RDW [ 45 ]. Their study showed that RDW was associated with brain natriuretic peptide in DM patients with HF.…”
Section: Rbc Parametersmentioning
confidence: 99%
“…Based on several studies, RDW is a marker of inflammation and prognosis in T2DM patients [ 43 , 44 ]. Subharshree et al initially examined the relationship between T2DM and RDW [ 45 ]. Their study showed that RDW was associated with brain natriuretic peptide in DM patients with HF.…”
Section: Rbc Parametersmentioning
confidence: 99%